The Effect of Attentional Focus and Frequency of Feedback on Performance and Kinematics in Basketball Free Throwing - Majid Pahlevanyali; Mehdi Shahbazi; Seyed Mehdi Aghapour-Hasiri; Shahzad Tahmasebi-Boroujeni; Ali Shamsi-Majelan (Vesnu Publications, 2018)
Introduction: The purpose of this study was to investigate the effect of attentional focus and frequency of feedback on performance and kinematics in basketball free throwing. Materials and Methods: In this semi-experimental research, fifty students were randomly selected using convenience sampling method, and were randomly divided in one control and 4 experimental groups (internal focus and 33% feedback, internal focus and 100% feedback, external focus and 33% feedback, and external focus and 100% feedback). Experimental groups conducted six blocks of ten attempts (every day two blocks of ten attempts) in one week, and in three sessions of training, and received internal or external focus feedback with the corresponding frequency (33% or 100%). After 72 hours, retention and transfer tests were performed with ten-attempt blocks. Performance (throwing accuracy) and kinematic data (joint angle and range of motion) were collected. Data were analyzed using ANOVA with repeated measures and one way ANOVA. Results: Feedback with external focus (100% and 33%) was more effective in improving throwing performance in retention and transfer tests (P < 0.050). Kinematic data analysis showed that external focus feedback groups had the least maximum flexion in the knee joint in retention test compare to acquisition stage (P < 0.050). Moreover, external focus groups had the least maximum flexion at the knee in retention test compared to internal focus groups (P < 0.050). In range of motion of the knee, external focus groups had more range of motion in retention and transfer tests compared to internal focus groups (P < 0.050). Conclusion: Performance improvement in external focus groups may be limited to certain changes in kinematic data, and in line with constrained-action hypothesis.